Preparation of Grease using Organic Thickener - Nur Suhaila, Anang Japar; Mohd Aizudin, Abd Aziz; Mohd Najib, Razali; Nur Aini Liyana, Zakaria; Nurul Waheeda, Abdu Rahman (Elsevier Ltd, 2019)
This paper aimed to study of the behaviour of organic thickener in the grease formulation. In this study different types of organic thickener (polypropylene, chitosan, cellulose) with different percentage has been tested in grease formulation. The percentage of base oil and thickener used were 65 to 75% of base oil and 25 to 35% of thickener. The formulation was done by dispersing the thickener in the base oil at temperature of 110°C for 3 hours. Several tests were conducted to evaluate the grease properties, including its consistency, oil bleeding, and oil separation. It was found that polypropylene-thickened grease shows most desirable properties with consistency of NLGI no. 1, > -15% of oil bleeding and < 4% of oil separation, compared to other organic thickener. It was shown that 70 – 75% of base oil with 25 to 30% of polypropylene thickener were the best formulation. However, all of the formulated greases were unable to withstand high temperature as it tends to fully liquefied.